Learning from prices: Amplification and business fluctuations - Ryan Chahrour; Gaetano Gaballo (European Central Bank (ECB), 2017)
We provide a new theory of expectations-driven business cycles in which consumers' learning from prices dramatically alters the effects of aggregate shocks. Learning from prices causes changes in aggregate productivity to shift aggregate beliefs, generating positive price-quantity comovement. The feedback of beliefs into prices can be so strong that even arbitrarily small productivity shocks lead to substantial fluctuations. Augmented with a public signal, the model can generate a rich mix of supply- and demand-driven fluctuations even though productivity is the only source of aggregate randomness. Our results imply that many standard identification assumptions used to disentangle supply and demand shocks may not be valid in environments in which agents learn from prices.
Keywords: D82; D83; E3; 330; expectations; animal spirits; incomplete information